Evaluation of life's quality of women in climacteric in the city of Floriano, Piauí - Daianne Vieira Menezes; Maria Evangelina de Oliveira
Abstract Introduction: The climacteric is the transition phase that is between the end of the reproductive and non-reproductive period of the woman's life, and that can be extended up to 65 years of age. Menopause is considered the mark of this phase and is characterized as an event, and not as a period. Objectives: To evaluate the life's quality of women in climacteric, in the city of Floriano - PI, by using the Women's Health Questionnaire (WHQ). With the specific objectives it was sought to identify the socio-demographic profile and menopausal status, highlight the most frequent symptoms at this phase and verify the intensity of climacteric symptoms in women through the Blatt-Kupperman Index (BKI). Methodology: It is a descriptive, cross-sectional and quantitative study. For the selection of the participating subjects, it was made a systematically count in every three domiciles in Nova Sambaíba neighborhood, in the city of Floriano, PI. The sample consisted of 184 women. Results: In the verification of the intensity of climacteric symptoms, given by Blatt-Kupperman Index (BKI), the symptomatology was considered light for 109 women (59.24%) and the most common symptoms were nervousness (73.9%), skin changes (66.8 %), anxiety (60.9%), hot flashes (57.6%), thinning and loss of hair (49.5%) and hypertension (26.1%). The most affected domain of the WHQ was the sexual function, with an average of 1.9, and the domains of menstrual problems and depressed mood, considered lighter (3.3). Conclusion: According to the applied methodology, it is concluded that the obtained data didn't show significant impairment of quality of life of these women because of climacteric.